2016
DOI: 10.9734/acsj/2016/22445
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Drinking Water Quality Using Water Quality Index in Ado-Ekiti and Environs, Nigeria

Abstract: This work was carried out in collaboration between all authors. Authors BMO, JOO and OF designed the study. Author BMO performed the statistical analysis, wrote the protocol and wrote the first draft of the manuscript. Authors BMO, JOO and OF managed the analyses of the study. Author OF managed the literature searches. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Turbidity, color, taste, and odor, whether natural or man-made, influence consumer perceptions and behavior (WHO, 1997;WHO, 2011). Studies evaluating the quality of drinking water in Nigeria are on a continuum (Oyelakin et al, 2020;Ibrahim et al, 2020;Olowe et al, 2016;Foka et al, 2018;Ince et al, 2010). This is critical for highlighting the dangers of unsafe drinking water that are available and proliferating in both urban and rural communities, as well as boosting consumer confidence in safe water sources.…”
Section: Jcbr Vol 2 Is 4 July-august 2022mentioning
confidence: 99%
“…Turbidity, color, taste, and odor, whether natural or man-made, influence consumer perceptions and behavior (WHO, 1997;WHO, 2011). Studies evaluating the quality of drinking water in Nigeria are on a continuum (Oyelakin et al, 2020;Ibrahim et al, 2020;Olowe et al, 2016;Foka et al, 2018;Ince et al, 2010). This is critical for highlighting the dangers of unsafe drinking water that are available and proliferating in both urban and rural communities, as well as boosting consumer confidence in safe water sources.…”
Section: Jcbr Vol 2 Is 4 July-august 2022mentioning
confidence: 99%
“…There are few studies reporting lead in groundwater from coastal basins of southwestern Nigeria. An assessment of drinking water quality using the Water Quality Index in Ado-Ekiti and environs, by Olowe, Oluyege [134], showed that Pb ranged from <0.001-7.0 mg/l with a mean value of 1.94 mg/l. The quality assessment of groundwater in the vicinity of dumpsites in Ifo and Lagos, Southwestern Nigeria by Majolagbe, Kasali [126], showed that Pb concentrations at Ifo were below the detection limit.…”
Section: Longe and Enekwechimentioning
confidence: 99%
“…Groundwater quality appraisals by Aribisala et al (2017); Oyedele et al (2019) among others on some selected hand-dug well, boreholes and spring water within Ado Ekiti metropolis, generated results, that were at disagreement with the permissible limit for potability set by the World Health Organization (WHO) and Nigerian Standard for Drinking Water Quality (NSDWQ). Olowe et al (2016) and others researched into the prevalence of water-related diseases arising from groundwater contaminations through anthropogenic activities in Nigeria and their works disabuse the conception that groundwater is impregnable to feacal coliform related contamination. The focus of this research is to study the impact of seasonal variations on well water quality especially in Ado -Ekiti metropolis as this will assist in creating awareness on groundwater quality for domestic consumption.…”
Section: Introductionmentioning
confidence: 99%